A new Mniotype Franclemont (Lepidoptera, Noctuidae) species from China - Gyulai, Peter; Saldaitis, Aidas (Zootaxa, 2016)
The Blepharita Hampson - Mniotype Franclemont—Polymixis Hübner - Mniopamea Hacker & Peks, generic complex is a favourite of Noctuidae researchers due to its richness in evolutional lineages, the debatable taxonomic placement of certain species among the first three genera and the taxonomic interpretation of the genera themselves. This rich and diverse complex includes some fairly separable species of which the taxonomic placement has been changed during the last decades, particularly as a result of the very similar basic configuration of the genitalia. The most relevant comprehensive studies on the generic complex are given by Boursin (1964), Varga (1979), Hacker (1990), Hacker & Peks (1990), Hacker (1992), Hacker & Ronkay (1992), Hreblay & Ronkay (1997, 1998), Hreblay et al. (1998), Hreblay & Ronkay (1999), Ronkay et al. (2001), Benedek & Ronkay (2002). The most recent study on the Mniotype adusta species graup is given by Volynkin et al. (2014), whereas on the Polymixis by Saldaitis et al. (2015). The fourth member of the complex namely Mniopamea, is the latest erected genera, of which the two described species by Hacker (1992) are close relatives of the formerly known Mniotype timida (Staudinger, 1888).